2011
DOI: 10.1371/journal.pone.0018956
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of 2009 Pandemic Influenza A(H1N1) Viruses Collected in Japan during the Peak Phase of the Pandemic

Abstract: BackgroundPandemic influenza A(H1N1) virus infection quickly circulated worldwide in 2009. In Japan, the first case was reported in May 2009, one month after its outbreak in Mexico. Thereafter, A(H1N1) infection spread widely throughout the country. It is of great importance to profile and understand the situation regarding viral mutations and their circulation in Japan to accumulate a knowledge base and to prepare clinical response platforms before a second pandemic (pdm) wave emerges.MethodologyA total of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
32
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 42 publications
10
32
1
Order By: Relevance
“…Some isolates identified in the present study also had low amino acid substitution rates (6.3z-18.8z) at positions I5R, L105W, N228D, V234L, V272I, T277A, K443E, S451N, and V527I, and a considerably high amino acid substitution rate (93.8z) at position E374K (Fig. 2, Table 2 H275Y and N295S mutations responsible for resistance to NA inhibitors (38,39) were not detected in any of the 16 isolates analyzed in this study (Table 1). (6).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Some isolates identified in the present study also had low amino acid substitution rates (6.3z-18.8z) at positions I5R, L105W, N228D, V234L, V272I, T277A, K443E, S451N, and V527I, and a considerably high amino acid substitution rate (93.8z) at position E374K (Fig. 2, Table 2 H275Y and N295S mutations responsible for resistance to NA inhibitors (38,39) were not detected in any of the 16 isolates analyzed in this study (Table 1). (6).…”
Section: Resultssupporting
confidence: 51%
“…Infections with oseltamivir-resistant strains have been reported in both sporadic cases and a limited number of clusters during the post-pandemic period in several studies (36,37). Oseltamivir resistance-related mutations, such as NA-H275Y and NA-N295S, have been reported elswhere (38,39). To date, reports have indicated that only a limited number of influenza A(H1N1)pdm09 strains (º1z) showed resistance to neuraminidase inhibitors (40).…”
Section: Resultsmentioning
confidence: 99%
“…HA-Asn185 is located in the Ca antigenic site [6], [21], being found in the HA protein of the reported sequences of the 1918 influenza viruses [22][23]. There was no mutation associated with oseltamivir-resistance in the NA segment in this patient (data not shown).…”
Section: Resultsmentioning
confidence: 69%
“…LAMP is mainly used for pathogen detection with rapid and accurate detection [32], whereas SmartAmp is a particularly useful method for SNP and mutation detection [16], [18]. It is well known that the His-to-Tyr substitution at amino acid residue 275 confers the 2009 pdm influenza A(H1N1) virus oseltamivir-resistance, and this mutation was detected in patients infected with 2009 pdm influenza A(H1N1) viruses in our clinical study [6]. It has been reported that the oseltamivir-resistant 2009 pdm influenza A(H1N1) viruses were as pathogenic and transmittable as their drug-sensitive counterparts [14].…”
Section: Discussionmentioning
confidence: 72%
“…According to Indian health officials, the pH1N1 strain has not changed much from the first strain that emerged in 2009 [20]. The phylogenetic analysis based on partial HA1 gene sequences of study strains revealed the presence of 2 mutations (S220T and S202T) in HA1 gene of all study strains which are specific to clade 7 genotype of pH1N1 [6,10,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%